Effects of dietary grapeseed extract on performance, energy and nitrogen balance as well as methane and nitrogen losses of lambs and goat kids - Sinz, Susanne; Leparmarai, Paul Taipa; Liesegang, Annette; Ortmann, S.; Kreuzer, M.; Marquardt, Svenja (Cambridge University Press, 2021)
The influence of phenol-rich dietary grapeseed extract on performance, energy and N balance and methane production was determined in sixteen lambs and thirteen goat kids (body weight 20·5 and 19·0 kg, 2 months of age, day 1 of study). Half of the animals received a concentrate containing grapeseed extract, and the others received concentrate without grapeseed extract (total extractable phenols analysed 27 v. 9 g/kg dietary DM; concentrate and hay 1:1). Diets were fed for 7 weeks with 1 week for determining intake, excretion and gaseous exchange in metabolism crates and respiration chambers. Overall, there was an adverse effect of the phenolic diet on apparent N digestibility and body N retention. Faecal N loss as proportion of N intake increased while urinary N loss declined. Relative to N intake, total N excretion was higher and body N retention lower in goat kids than lambs. Diets and animal species had no effect on methane emissions. The saliva of the goat kids had a higher binding capacity for condensed tannins (CT). Goat kids on the phenolic diet had higher CT concentrations in faeces and excreted more CT compared with the lambs (interaction species × diet P < 0·001). The lambs had overall higher (P < 0·001) urinary phenol concentrations than the goat kids (2·19 v. 1·48 g/l). The negative effect on body N retention and lack of effect on methane emissions make the use of the extract in the dosage applied not appealing. Species differences need to be considered in future studies.